2010
DOI: 10.1186/1476-7120-8-34
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of distal coronary flow reserve in LAD and LCx after Y-Graft intervention assessed by transthoracic echocardiography

Abstract: BackgroundY- graft (Y-G) is a graft formed by the Left Internal Mammary Artery (LIMA) connected to the Left Anterior Descending Artery (LAD) and by a free Right Internal Mammary Artery (RIMA) connected to LIMA and to a Marginal artery of Left Circumflex Artery (LCx). Aim of the work was to study the flow of this graft during a six months follow-up to assess whether the graft was able to meet the request of all the left coronary circulation, and to assess whether it could be done by evaluation of coronary flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…11 The coronary flow velocity reserve is also useful for evaluation after coronary artery bypass grafting. 12 In this study, it significantly decreased compared with that in the other groups without any significant stenotic lesions. Although the coronary artery flow of the left anterior descending artery at rest was preserved in the patients with coronary artery bypass grafting, the coronary flow velocity reserve did not necessarily improve after coronary artery bypass grafting.…”
Section: Discussionsupporting
confidence: 41%
“…11 The coronary flow velocity reserve is also useful for evaluation after coronary artery bypass grafting. 12 In this study, it significantly decreased compared with that in the other groups without any significant stenotic lesions. Although the coronary artery flow of the left anterior descending artery at rest was preserved in the patients with coronary artery bypass grafting, the coronary flow velocity reserve did not necessarily improve after coronary artery bypass grafting.…”
Section: Discussionsupporting
confidence: 41%
“…Yip et al concluded that LD is related to unsuccessful reperfusion and to a higher 30-day mortality rate in LCX infarct-related acute myocardial infarction (MI) patients [21]. In addition, Auriti et al showed that coronary flow reserve was more impaired in LCX than LAD just after Y-graft intervention, which was a graft formed by the left internal mammary artery (LIMA) connected to the LAD and by a free right internal mammary artery (RIMA) connected to LIMA and a marginal artery of the LCX [22]. Clinically, a recent study showed that the 30-day prognostic outcome was less favorable in LCX-related acute inferior MI compared to RCA-related acute inferior MI [23].…”
Section: Discussionmentioning
confidence: 99%